PENGEMBANGAN LEMBAR KERJA PESETA DIDIK BERBASIS STEM (SCIENCE, TECHNOLOGY, ENGINEERING AND MATHEMATICS) PADA MATERI TERMOKIMIA - Novia Nur Sakinah; Junifa Layla Sihombing; Susilawati Amdayani (JS (JURNAL SEKOLAH), 2022)
Abstract :Development of STEM-Based Student Worksheets (Science, Technology, Engineering And Mathematics) on Thermochemical Materials. This study aims to determine the level of feasibility, practicality, and student responses to STEM-based student worksheets on thermochemical material. The subjects of this study were 2 material expert validators and 2 media expert validators, 2 chemistry teachers and all students of class XI MIA 1. The research design used a 4-D model (Define, Design, Develop, and Disseminate). The instruments used are interview guidelines, validation sheets by validators, practicality questionnaires by teachers, and student response questionnaires. The data analysis technique used presentation method. The results obtained that the average percentage of assessment by material experts is 83.03% in the appropriate category, by media experts at 98.2% in the very appropriate category, the practicality level by the teacher is 98.5% in the very practical category, and the results of student responses is 94.44% answered "yes" and 5.56% answered "no" so that it shows the good category.Keywords: LKPD, STEM, Thermochemistry, 4-D ModelAbstrak : Pengembangan Lembar Kerja Peseta Didik Berbasis STEM (Science, Technology, Engineering And Mathematics) Pada Materi Termokimia. Penelitian ini bertujuan untuk mengetahui tingkat kelayakan, praktikalitas, dan respon peserta didik tehadap lembar kerja peserta didik berbasis STEM pada materi termokimia. Subjek dari penelitian ini adalah 2 orang validator ahli materi dan 2 orang validator ahli media, 2 orang guru kimia dan seluruh siswa kelas XI MIA 1. Desain penelitian menggunakan model 4-D (Define (Pendefinisian), Design (Perancangan), Develop (Pengembangan), dan Disseminate (Penyebaran)). Intrumen yang digunakan berupa pedoman wawancara, lembar validasi oleh validator, lembar angket praktikalitas oleh guru, dan lembar angket respon siswa. Teknik analisis data menggunakan metode presentase. Hasil penelitian diperoleh rata-rata presentase penilaian oleh ahli materi sebesar 83.03% dengan kategori layak, oleh ahli media sebesar 98,2% dengan kategori sangat layak, tingkat kepraktikalitas oleh guru adalah 98,5% dengan kategori sangat praktis, dan hasil respon peserta didik adalah 94,44% menjawab “ya” dan 5,56% menjawab “tidak” sehingga menunjukkan kategori baik.Kata Kunci : LKPD, STEM, Termokimia, Model 4-D